2016
DOI: 10.1111/1751-7915.12450
|View full text |Cite
|
Sign up to set email alerts
|

Microbial copper resistance: importance in biohydrometallurgy

Abstract: SummaryIndustrial biomining has been extensively used for many years to recover valuable metals such as copper, gold, uranium and others. Furthermore, microorganisms involved in these processes can also be used to bioremediate places contaminated with acid and metals. These uses are possible due to the great metal resistance that these extreme acidophilic microorganisms possess. In this review, the most recent findings related to copper resistance mechanisms of bacteria and archaea related to biohydrometallurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 105 publications
(236 reference statements)
0
38
0
Order By: Relevance
“…Acidophilic bacteria used in biomining processes have developed diverse strategies to cope with high metal ions concentrations, including active mechanisms also present in neutrophilic microorganisms, as well as passive mechanisms, such as complexation of metal ions with sulfate (Baillet et al, 1997 ; Dopson and Holmes, 2014 ). In addition, resistance to heavy metals like copper and cadmium has been related to the synthesis/degradation of inorganic phosphate granules (polyphosphate, or polyP) in Acidithiobacillus ferrooxidans (Dopson et al, 2003 ; Alvarez and Jerez, 2004 ; Martínez-Bussenius et al, 2017 ). In this model, when bacterial cells are grown in presence of high metal concentrations, there is a decrease in polyP levels and a concomitant formation of metal-phosphate complexes that contribute to detoxification (Dopson et al, 2003 ; Alvarez and Jerez, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acidophilic bacteria used in biomining processes have developed diverse strategies to cope with high metal ions concentrations, including active mechanisms also present in neutrophilic microorganisms, as well as passive mechanisms, such as complexation of metal ions with sulfate (Baillet et al, 1997 ; Dopson and Holmes, 2014 ). In addition, resistance to heavy metals like copper and cadmium has been related to the synthesis/degradation of inorganic phosphate granules (polyphosphate, or polyP) in Acidithiobacillus ferrooxidans (Dopson et al, 2003 ; Alvarez and Jerez, 2004 ; Martínez-Bussenius et al, 2017 ). In this model, when bacterial cells are grown in presence of high metal concentrations, there is a decrease in polyP levels and a concomitant formation of metal-phosphate complexes that contribute to detoxification (Dopson et al, 2003 ; Alvarez and Jerez, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, while PPX homologs were identified within the Crenarchaeota, concentrated in the order Sulfolobales, no PPK1 or 2 homologs were retrieved from this taxon. Martinez-Bussenius et al 53 has previously shown the presence of ppx but not ppk1 in 6 species of Sulfolobus sp., and Metallosphaera sedula.…”
Section: Discussionmentioning
confidence: 97%
“…To prevent cellular damage, all cells have developed various copper detoxification strategies. In prokaryotes, this is mainly achieved by active export of copper ions and in rarer cases by sequestration or exclusion (12,17).…”
Section: Introductionmentioning
confidence: 99%